DETERMINANTS AFFECT MOBILE WALLET CONTINUOUS USAGE IN COVID 19 PANDEMIC: EVIDENCE FROM VIETNAM - Huynh Thi Ngoc Ly; Nguyen Vinh Khuong; Tran Hung Son (Cogent Business & Management, 2022)
Disruptive technology has been prominent as a spotlight with countless innovations that improve human’s life efficiently. In Vietnam, COVID-19ʹs outbreak has reinforced citizens to adopt other types of payment without using cash, which easily diffuses virus. Till now, the number of studies related to continuance usage of mobile wallets in Vietnam has been rare. Hence, our purpose in this research is to study continuance usage in COVID-19 through determinants. This paper concentrates on Millennials and Zillennials living Ho Chi Minh City. PLS-SEM with data collected from questionnaires assesses the conceptual model that indicates the correlation between UTAUT2ʹs constructs, trust, price saving orientation, behavioral intention and continuance usage. As predicted, the findings show that there are positive relationships among all determinants. In the event of effort expectancy and social influence, despite unsatisfactory of statistical significance, they reflect current context. Besides, direct positive influences from two variables to behavioral intention lead to further research studies after the pandemic to conclude properly about their significance. From the study’s result, business strategies together with security’s policies have to be modified by providers as well as the government to motivate mobile wallet adoption in Vietnam, amplifying cashless society and financial inclusion targets.